Enterococcus faecium GEFA01 alleviates hypercholesterolemia by promoting reverse cholesterol transportation via modulating the gut microbiota-SCFA axis - Xu, Wenfeng; Zou, Kaixiang; Zhan, Ying; Cai, Yunjie; Zhang, Zhihong; Tao, Xueying; Qiu, Liang; Wei, Hua (Frontiers in Nutrition, 2022)
This study aimed to identify cholesterol-lowering commensal strains from healthy lean individuals and to evaluate the cholesterol-lowering capacity of Enterococcus faecium GEFA01 in mice fed a high-cholesterol and high-fat diet. E. faecium GEFA01 was isolated from the feces of a healthy lean individual in a selective basal salt medium supplemented with cholesterol. E. faecium GEFA01 exhibited a cholesterol removal rate (CRR) of 46.13% by coprecipitation, assimilation, and degradation of cholesterol. Moreover, E. faecium GEFA01 significantly decreased the body weight of mice and the levels of serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), hepatic TC, triglycerides (TG), and LDL-C, and increased serum high-density lipoprotein cholesterol (HDL-C) levels in mice fed a high-cholesterol diet compared with the HCD group. We also observed that E. faecium GEFA01 significantly downregulated the gene expression of HMG-CoA reductase (Hmgcr), Srebp-1c, Fxr, Shp, and Fgf 15, upregulated the gene expression of low-density lipoprotein receptor (Ldlr), Abcg5/8, Abca1, cholesterol 7 alpha-hydroxylase (Cyp7a1), and Lxr in the liver of mice in relative to the HCD group, markedly increased the relative abundance of Lactobacillus, Akkermansia, Bifidobacterium, and Roseburia, and decreased the abundance of Helicobacter in the feces. Collectively, we confirmed that E. faecium GEFA01 exhibited cholesterol-lowering effects in mice fed a high-cholesterol diet, which was achieved through assimilation, coprecipitation, and degradation of cholesterol, and through modulation of the gut microbiota short-chain fatty acid (SCFA) axis that promoted reverse cholesterol transport and bile acid excretion. Our study demonstrated that E. faecium GEFA01 may be used as a probiotic candidate to lower cholesterol levels in the future.